DEFENCE COOPERATION BETWEEN INDOENSIA AND GERMANY IN AIR DEFENCE: A STUDY ON DIEHL DEFENCE’S IRIS-T MISSILE - Haryanto, Teguh Dwi; Dermawan, Windy; Sari, Deasy Silvya (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Indonesia faces various forms of potential threats from outside and from within the country which also includes airspace. The Indonesian Air Force as a state instrument in the field of air defence has a duty, which one of it is to maintain sovereignty in the airspace of national jurisdiction using combat aircraft in carrying out air defence and taking action against airspace violations. However, in reality, the current condition of air missiles owned by the Air Force is still very limited in number to support operations and the trend of readiness has decreased, so that it is necessary to increase the strength of defense equipment through defence cooperation that needs to be carried out by Indonesia with Germany in the acquisition of IRIS-T missiles. This research uses a qualitative method. The required data were collected through interviews with a number of relevant informants, observation, literature study and documentation. The data obtained in the research were then analysed through three stages of analysis, namely data reduction, processing and analysis, data presentation, and conclusion drawing. The results showed that defence cooperation between Indonesia and Germany in the acquisition of IRIS-T missiles is possible and feasible. If the Indonesian Air Force acquires IRIS-T missiles, there will be compatibility with air defence systems owned by fighter aircraft such as the F-16 AM/BM emlu, F-16 C/D and T-50i aircraft. There are four opportunities if the IRIS-T acquisition is carried out, namely increased missile capability, flexibility and interoperability, deterrence and trust and modernisation and technology.